Pengaruh Dimensi Indeks Pengelolaan Keuangan Daerah terhadap Kinerja Pengelolaan Keuangan Pemerintah Kota Kupang - Yehezkiel Arya Ruku; Anthon S.Y Kerihi; Olivia L. E. Tomasowa (AKUNTANSI 45, 2026)
This study was motivated by the implementation of regional autonomy, which grants local governments the authority to manage their finances independently in a transparent and effective manner. The existence of phenomena and research gaps in previous studies indicates that problems in regional financial management still persist. Therefore, this study aims to examine the six dimensions of the Regional Financial Management Index (IPKD) in an integrated manner. This research employed a quantitative descriptive approach to analyze phenomena related to the Regional Financial Management Index (IPKD). The results of the study show that:(1) The alignment between planning and budgeting documents does not have a significant effect on financial performance because governments tend to adjust to actual needs. (2) The allocation of the regional budget (APBD) does not determine performance, but rather the effectiveness and efficiency of its management have a greater influence; (3) Regional financial transparency has not had a significant impact because it is still largely administrative in nature;(4) Budget absorption does not reflect good performance because it focuses more on outputs rather than outcomes;(5) Regional financial conditions have a positive and significant effect on financial management performance. The better the financial condition of a region, the greater the government’s ability to manage finances effectively and sustainably;(6) The audit opinion of the Audit Board of Indonesia (BPK) on regional government financial statements (LKPD) has a positive effect because it reflects accountable financial management.